BIODIVERSIDADE E ESTRUTURA ARBÓREA DO ESTRATO REGENERANTE EM UM POVOAMENTO DE Eucalyptus spp - COLINA, SP - Marmontel, Caio Vinicius Ferreira; Mutti, Hevandro Sanches; Martins & Martins, Thiago; Rodrigues, João Paulo; Rodrigues, Valdemir Antonio (Electronic Journal "Fórum Ambiental da Alta Paulista", 2011)
.